ECG-Based Techniques to Optimize Peripherally Inserted Central Catheters: Rationale for Tip Positioning and Practical Use - Gullo, Giuseppe; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2022)
Intracavitary electrocardiography is an accurate guidance technique for peripherally inserted central catheters (PICC) tip location that is spreading widely among providers using non x-ray-based facilities. The principle behind this technology relies on the transmission of the electrocardiographic signal at the tip of the catheter and its use as an internal mobile electrode, allowing the system to identify the cavo-atrial junction (CAJ) through internal P-wave amplitude modulations. The gain in popularity of intracavitary electrography and its large diffusion have led manufacturers to offer various devices with heterogeneous properties, among which clinician who place PICCs have to choose. It is therefore important to understand differences between available techniques and devices. The potential impact might not only affect availability and costs but also the clinical impact through advantages and limitations regarding electric signal transmission PICC selection. Current perspectives on intracavitary electrocardiography will also be discussed, to give the reader a global view of the management of electrocardiographically guided PICCs, especially in an environment without x-ray support.